Recent Research on Indexation and the Housing Market: Discussion - Edelstein, Robert H. (Journal of Finance, 1976)
Robert H. Edelstein, Recent Research on Indexation and the Housing Market: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 443-446